ANALISIS OPTIMALISASI PENGADAAN TANDAN BUAH SEGAR (TBS) SEBAGAI BAHAN BAKU PRODUKSI CRUDE PALM OIL (CPO) DAN PALM KERNEL (PK)DI PMKS SEI KANDANG PT. ASIATIC PERSADA-AMS GROUP - Renta Renta (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract. As an agribusiness palm oil company, PT. AMS through its subsidiary, PT. AsiaticPersada, aims to increase the company's profits from sales of CPO and Kernel processed inPMKSei Kandang. Availability of raw materials fresh fruit bunches (FFB) POM Sei Kandangare not optimal so that the production of CPO and PK also not optimal, and then thecompany's profits are not maximized. This study aims to providea recommendation foroptimizing procurement TBS with the concept of linear programming (LP). Through optimalapproach EOQ TBS purchases outside during 2014 was still below the optimal standard soPMKSs Sei Kandang should do a combination of raw material procurement policy TBS fromits own garden and make purchases outside.Keywords: optimization, linear programming, CPO, kernel, FFB